2009
DOI: 10.1111/j.1439-0507.2008.01603.x
|View full text |Cite
|
Sign up to set email alerts
|

Commonly affected body sites in 92 Japanese combat sports participants with Trichophyton tonsurans infection

Abstract: Outbreaks of Trichophyton tonsurans infection constitute one of the serious problems among combat sports practitioners in Japan. To facilitate the diagnosis of individuals at risk, we undertook a study to determine which body sites are most commonly infected. We reviewed medical data, hairbrush culture results and questionnaire information from patients with T. tonsurans infection who were admitted to the dermatology clinic of Juntendo University hospital from 2000 to 2004. The study included 92 patients (87 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 18 publications
0
31
0
1
Order By: Relevance
“…Of these, 19 were solitary reports of an outbreak in a single sport [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] ; 3 (including 2 from Juntendo University 24,25 ) addressed a tinea epidemic due to Tricophyton tonsurans among combat-sport (mainly judo, although one also included wrestlers 26 ) competitors in Japan [24][25][26] ; 1 reported on a single measles virus outbreak involving competitors in 2 sports;hairsp 27 ; and 1 discussed the importance of sentinel surveillance sites in high school athletic departments to monitor outbreaks of CA-MRSA across a variety of sports. 28 When we excluded this latter study from analysis (because its main focus was not a specific outbreak) and counted the 3 articles on the tinea outbreak among combatsport competitors in Japan as a single outbreak, a total of 21 outbreaks or clusters were reported in the time period.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 19 were solitary reports of an outbreak in a single sport [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] ; 3 (including 2 from Juntendo University 24,25 ) addressed a tinea epidemic due to Tricophyton tonsurans among combat-sport (mainly judo, although one also included wrestlers 26 ) competitors in Japan [24][25][26] ; 1 reported on a single measles virus outbreak involving competitors in 2 sports;hairsp 27 ; and 1 discussed the importance of sentinel surveillance sites in high school athletic departments to monitor outbreaks of CA-MRSA across a variety of sports. 28 When we excluded this latter study from analysis (because its main focus was not a specific outbreak) and counted the 3 articles on the tinea outbreak among combatsport competitors in Japan as a single outbreak, a total of 21 outbreaks or clusters were reported in the time period.…”
Section: Resultsmentioning
confidence: 99%
“…We analyzed a total of 92 patients with T. tonsurans infection who visited a dermatology clinic of a university hospital during a 5‐year period from 2000 to 2004. For judo practitioners, we found that the commonly affected body sites are the hairline in the occipitotemporal region and sites that rub against the judo uniform during judo practice …”
Section: Clinical Features Of T Tonsurans Infectionmentioning
confidence: 96%
“…Contact sports involve close skin‐to‐skin contact, facilitating the transmission of dermatophytes between competitors and team members 2–11 . Recent studies have revealed that, although it is not spreading rapidly, T .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the incidence of tinea cruris and tinea pedis does not differ across combat and non‐combat sports 1 . The anthropophilic dermatophyte Trichophyton tonsurans is an emerging pathogen that is responsible for several tinea gladiatorum outbreaks in North America, 2,3 as well as Europe, 4–7 the Middle‐East 8–10 and Japan 11 . These worldwide outbreaks reflect the potential spread of this fungus across contact sports players.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation